Staged magnetic resonance-guided focused ultrasound thalamotomy for the treatment of bilateral essential tremor and Parkinson’s disease related tremor: a systematic review and critical appraisal of current knowledge - Cesarano, Simone; Saporito, Gennaro; Sucapane, Patrizia; Bruno, Federico; Catalucci, Alessia; Pistoia, Maria Letizia; Splendiani, Alessandra; Ricci, Alessandro; Di Cesare, Ernesto; Totaro, Rocco; Pistoia, Francesca (Frontiers in Neurology, 2024)
Introduction Essential tremor (ET) and Parkinson’s Disease (PD) are debilitating neurodegenerative disorders characterized by tremor as a predominant symptom, significantly impacting patients’ quality of life. Magnetic Resonance-guided Focused Ultrasound (MRgFUS) Thalamotomy is an innovative therapeutic option for the treatment of unilateral medically refractory tremor with fewer adverse effects compared to traditional surgical interventions. A recent CE approval allows appropriate patients to have their second side treated. Objective The objective of this systematic review was to analyze available current knowledge about the use of MRgFUS for the treatment of bilateral ET and PD related tremor, to identify the effectiveness and the risks associated with bilateral treatment. Methods Eligible studies were identified by searching published studies in PubMed and Scopus databases from May 2014 to January 2024 and by identifying ongoing studies registered on the clinicaltrials.gov website. Data were summarized by considering the following information topics: the number of patients involved, the selected lesion target, the assessment tool used to evaluate clinical changes, the observed improvement, the reported side effects, and the time interval between the two treatments. The study was registered in PROSPERO (ID: CRD42024513178). Results Nine studies were eligible for this review, 7 for ET and 2 for PD. The involved population included a variable number of patients, ranging from 1 to 11 subjects for ET and from 10 to 15 subjects for PD. The main lesional targets were the ventral intermediate nucleus of the thalamus, the pallidothalamic tract and the cerebellothalamic tract bilaterally. All studies investigated the tremor relief through the Clinical Rating Scale for Tremor (CRST) in patients with ET, and through the Unified Parkinson’s Disease Rating Scale (UPDRS) in patients with PD. A variable degree of improvement was observed, with all patients expressing overall satisfaction with the bilateral treatment. Adverse events were mild and transient, primarily involving gait disturbances, dysarthria, and ataxia. A standardized protocol for administering the two consecutive treatments was not identifiable; typically, the timing of the second treatment was delayed by at least 6 months. Conclusion Available evidence supports the effectiveness and safety of staged bilateral MRgFUS treatments for ET and PD-related tremor.